2020
DOI: 10.1155/2020/4783062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of 95 Patients with Different Severity in the Early Outbreak of COVID-19 in Wuhan, China

Abstract: Objective. To explore the clinical characteristics of patients with different severity in the early outbreak of COVID-19, hoping to provide reference for clinical diagnosis and treatment. Methods. We retrospectively analyzed the clinical data of 95 COVID-19 patients in Wuhan Red Cross Hospital of China from January 17 to February 13, 2020. All patients were investigated with epidemiological questionnaires. Outcomes were followed up until April 1, 2020. Results. There were 53 males and 42 females, aged 22–84 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…On the other hand, two meta-analyses found no association between diabetes and severe COVID-19 (Jain & Yuan, 2020;Yang et al, 2020a). Regarding the risk of mortality, similar results were observed in the metaanalyses conducted by and Tian et al (2020), in which diabetic patients were associated with a 3-and 2-fold higher risk of mortality from COVID-19, respectively (Tian et al, 2020b;Wu et al, 2020b). In addition, a meta-analysis carried out by Zheng et al (2020) revealed that diabetes was associated with a 3.68-fold higher risk of developing the critical form of COVID-19 or death from the disease (Zheng et al, 2020c).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…On the other hand, two meta-analyses found no association between diabetes and severe COVID-19 (Jain & Yuan, 2020;Yang et al, 2020a). Regarding the risk of mortality, similar results were observed in the metaanalyses conducted by and Tian et al (2020), in which diabetic patients were associated with a 3-and 2-fold higher risk of mortality from COVID-19, respectively (Tian et al, 2020b;Wu et al, 2020b). In addition, a meta-analysis carried out by Zheng et al (2020) revealed that diabetes was associated with a 3.68-fold higher risk of developing the critical form of COVID-19 or death from the disease (Zheng et al, 2020c).…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, the meta-analysis conducted by Tian et al (2020) revealed that patients with chronic kidney disease had a 9.40fold higher risk of death from COVID-19 (Tian et al, 2020b). In contrast, a previous meta-analysis found no association between chronic kidney disease and severe COVID-19, but the small number of studies (4 studies) and patients (n = 15) included may have influenced this analysis (Wang et al, 2020d).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations